The Reve’s Puzzle with a single cheat of the Divine rule - Majumdar, Abdullah Al Kafi (Journal of Bangladesh Academy of Sciences, 2024)
A new variant of the Reve’s puzzle, which allows (at most) one violation (or, “cheat”) of the “divine rule”, has been introduced in an earlier paper. Letting S(n) be the minimum number of moves required to solve the new generalization with n discs, this paper finds an explicit expression of S(n), taking into account all the possible schemes. Some results related to the generalization to the general case of c cheats are derived. J. Bangladesh Acad. Sci. 48(2); 251-264: December 2024